2006
DOI: 10.1530/rep.1.00847
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of dynamic events by microfilaments during oocyte maturation and fertilization

Abstract: Actin filaments (microfilaments) regulate various dynamic events during oocyte meiotic maturation and fertilization. In most species, microfilaments are not required for germinal vesicle breakdown and meiotic spindle formation, but they mediate peripheral nucleus (chromosome) migration, cortical spindle anchorage, homologous chromosome separation, cortex development/maintenance, polarity establishment, and first polar body emission during oocyte maturation. Peripheral cortical granule migration is controlled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
190
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(201 citation statements)
references
References 110 publications
6
190
1
4
Order By: Relevance
“…The cortex of mouse oocytes has no apparent polarity at the GV stage, but undergoes local reorganization and polarization during meiotic spindle migration to the cortex [1,3,4]. In this study, we found that cortical LGN was also polarized during this process.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…The cortex of mouse oocytes has no apparent polarity at the GV stage, but undergoes local reorganization and polarization during meiotic spindle migration to the cortex [1,3,4]. In this study, we found that cortical LGN was also polarized during this process.…”
Section: Discussionmentioning
confidence: 49%
“…In mouse oocytes, LGN cortical localization may also be mediated by interaction with the cortical heterotrimeric G protein α-subunits. Interestingly, the polarization pattern of cortical LGN is distinct from several identified polarity proteins (such as conserved polarity mediators Par3 and Par6, and the small GTPases Rac and Cdc42), which are concentrated at the actin cap region [7][8][9][10], whereas it is similar to those of cortical granules and microvilli [1,4]. The specific function of cortical polarized LGN has not been elucidated, In Drosophila neuroblasts and C. elegans one-cell embryos, Pins or its counterparts regulate spindle orientation and positioning and thus asymmetric cell division, but do not affect spindle organization [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of iNOS on the periphery of oocytes is not surprising with regard to the well-known association of iNOS with sub-membranous cortical actin cytoskeleton in somatic cells (Webb et al, 2001) and the presence of cortical actin cytoskeleton in oocytes (Sun and Schatten, 2006). This peripheral localization is probably important for the propagation of NO-signalling in somatic cells (Webb et al, 2001), and we cannot exclude that it is also important for oocytes.…”
Section: Discussionmentioning
confidence: 79%
“…27 During mouse oocyte meiotic maturation, actin was required for the chromosome migration, 9,28 cortical spindle anchorage, 29,30 cortex development and polarity establishment 2,31 and first polar body extrusion. 6,27 Additionally, some actin nucleation factors such as Arp2/3 complex, 6 Formin2 7,29 and Spire1/2 32 were involved in the actin organization during mouse oocyte maturation. Previous work showed that myosin II was activated by phosphorylation of its regulatory MLC at Ser19/Thr18, and the phosphorylation at MLC Ser19 was critical for actin assembly.…”
Section: Discussionmentioning
confidence: 99%